2016
DOI: 10.1007/s00423-016-1395-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic risk factors of early gastric cancer—a western experience

Abstract: ER within the extended criteria with a meticulous histological workup should be performed in EGC to determine whether risk factors for LNM are present. If lymphatic infiltration is observed, surgery with lymphadenectomy is recommended. Tumors exceeding the extended criteria should undergo primary surgery with adequate lymphadenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…The degree of tumor differentiation is a predictive and prognosis biomarker for patients with gastric cancer [ 29 ], which can be distinguished quantitatively by dual-energy spectral CT (DESCT). Pan et al [ 12 ] evaluated the clinical usefulness of DESCT in the classification and staging of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of tumor differentiation is a predictive and prognosis biomarker for patients with gastric cancer [ 29 ], which can be distinguished quantitatively by dual-energy spectral CT (DESCT). Pan et al [ 12 ] evaluated the clinical usefulness of DESCT in the classification and staging of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…et al [ 23 ] Brazil 2014 26 16.7% 42.9% Not available Fukuhara S. et al [ 10 ] USA 2014 104 7.1% 35.4% Lymphovascular invasion, non-Asian race and younger age. Haist T. et al [ 22 ] Germany 2016 124 1.9% 22.5% Depth of invasion, lymphovascular invasion. Ahmad R. et al [ 18 ] USA 2016 67 4.3% 31.8% Lymphovascular invasion and positive nodal status by endoscopic ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Up to this date, evidence of a correlation between lymphatic invasion and worse survival results have been demonstrated only by studies performed in Asia, with Western studies confirming these findings. Haist et al analyzed lymphatic invasion and survival result correlation in a Western cohort, however they did not display a significant effect of lymphatic invasion on longtime survival results [ 22 ]. Consequently, our study became the first of such Western reports to present lymphovascular invasion as an independent prognostic factor associated with worse long-term survival results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the above findings, most of the reports, including a large meta-analysis by Petrelli et al involving 50 studies and 128,268 patients with gastric cancer, showed that a location in the upper third part of the stomach was connected with an increased risk of tumor-related death and poorer 5-year survival rate (15,33,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 71%